2017
DOI: 10.1155/2017/1691568
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Green Tea (Camellia sinensis (L.) Kuntze) against Prostate Cancer: From In Vitro Data to Algerian Patients

Abstract: Green tea (GT) has been studied for its effects as antioxidant and cancer-preventive agent. Epidemiological studies showed that GT consumption decreases the risk for prostate cancer (PC). To investigate whether erythrocyte oxidative stress (OS) is associated with PC and whether daily consumption of GT improves the oxidative phenotype, we performed a study in a group of Algerian PC patients, preceded by an in vitro study to characterize composition and antioxidant/antiproliferative activities of the GT used. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…In a recent case-control involving Vietnamese men, increasing tea consumption (>500 ml/day) was found to be associated with decreased risk of prostate cancer [84]. Similar findings were reported in a case-control study of Algerian men, although the results were borderline statistically [80]. In one of the first clinical Dietary Antioxidants in the Chemoprevention of Prostate Cancer DOI: http://dx.doi.org /10.5772/intechopen.85770 studies to examine the effect of polyphenols (from green tea) on prostate cancer, Betuzzi and colleagues showed that green tea consumption reduces the incidence of prostate cancer in men with high-grade prostate intraepithelial neoplasia (HGPIN).…”
Section: Green Teasupporting
confidence: 73%
See 1 more Smart Citation
“…In a recent case-control involving Vietnamese men, increasing tea consumption (>500 ml/day) was found to be associated with decreased risk of prostate cancer [84]. Similar findings were reported in a case-control study of Algerian men, although the results were borderline statistically [80]. In one of the first clinical Dietary Antioxidants in the Chemoprevention of Prostate Cancer DOI: http://dx.doi.org /10.5772/intechopen.85770 studies to examine the effect of polyphenols (from green tea) on prostate cancer, Betuzzi and colleagues showed that green tea consumption reduces the incidence of prostate cancer in men with high-grade prostate intraepithelial neoplasia (HGPIN).…”
Section: Green Teasupporting
confidence: 73%
“…Green tea (GT) is one of the most widely studied source of phenolic acids such epigallocatechin-3-gallate (EGCG), epicatechin-3-gallate (ECG), and epicatechin (EC). There are a number of studies that have investigated the relationship between risk of prostate cancer and green tea [78][79][80][81][82], and preclinical, clinical, and epidemiological data suggest that green tea catechins may reduce prostate cancer risk [83]. In a recent case-control study of Chinese men, epigallocatechin 3-gallate and green tea reduced the risk of prostate cancer; however, the authors indicated that these results should be replicated in larger cohort or case-control studies [84].…”
Section: Green Teamentioning
confidence: 99%
“…In a previous study, the authors showed that green tea inhibited proliferation and also induced apoptosis in 4TI metastatic breast cancer cells (6) The authors have shown in a study that green tea can regulate the antioxidant capacity in people exposed to oxidative stress (25). Besides, C. sinensis decreased oxidative stress in patients with prostate cancer (26). In a study, it was suggested that green tea showed protective effects through its antioxidant properties against oxidative stress and DNA damages, (27).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative damage can be cured with phytochemicals found in tea in diseases such as cancer (15,22). Healing properties of C. sinensis have been investigated in many types of cancers such as metastatic breast (6), human ovarian 7, lung (23), and prostate cancers (8). The effects of C. sinensis were investigated in pancreatic carcinoma cells (9,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation